Treatment of Unstable Ankle Fractures - Yaniel Truffín Rodríguez; Gerardo Águila Tejeda (Medisur)
Patients with unstable ankle fractures frequently attend the emergency rooms. It is estimated that there are 122 ankle fractures per 100 000 people a year. Surgical treatment of those that are unstable is inevitable since they can not be corrected in a conservative way. Several surgical procedures for repair of such lesions have been described and all of them constitute important tools for the orthopedic surgeon. Therefore, we conducted a literature review to discuss the current management of unstable ankle fractures based on the analysis of the published literature and the experiences in the Dr. Gustavo Aldereguía Lima University General Hospital of Cienfuegos.